Ensuring Sustainable Livelihood for the Workers for the Sustainable Development in Ready Made Garments Industry in Bangladesh: An Empirical Study - Hossain, Tazia (International Journal For Research In Educational Studies, 2021)
Abstract: For the last few decades Bangladesh export oriented Ready Made Garments (RMG) sector has made significant contribution to country’s economic development and earning foreign exchange. All this progress will come undone unless Bangladesh can make ensure sustainable livelihood for garments workers. It is high time to give concern in poverty alleviation as well as overcoming vulnerability among workers. If sustainable livelihood is not ensure for marginal level workers, no sustainable development of workers like training program, career development program, performance management development which are the indicators of Human Resource Development is possible. As a result sustainable development in RMG Industry can’t be ensured. So, in the first stage, this study attempted to explore workers sustainable livelihood considering their income along with expenditure in basic needs. Most of the marginal workers have to expense all the income to manage minimum food and shelter for family. So there is no option of education, medicine or recreation. For this study, relevant data were collected from garments workers on Tongi, Gazipur commercial area. Both qualitative and quantitative analyses were done to achieve the objectives. It is found that socio economic condition of garment workers is not in a sustainable stage. Workers who work down to dusk but their wages are not in the satisfactory level. They cannot afford their minimum foods, cloths, housing, medicines and educations of their children as they are ill paid. Their children suffer from malnutrition and unhygienic complexities. At the end, some recommendations were placed for sustainable livelihood for the workers for the sustainable development in RMG industry in Bangladesh.